Phase I/II open-label trial of intravenous allogeneic mesenchymal stromal cell therapy in adults with recessive dystrophic epidermolysis bullosa - Rashidghamat, Ellie; Kadiyirire, Tendai; Ayis, Salma; Petrof, Gabriela; Liu, Lu; Pullabhatla, Venu; Ainali, Chrysanthi; Guy, Alyson; Aristodemou, Sophia; McMillan, James R.; Ozoemena, Linda; Mee, John; et al. (Journal of the American Academy of Dermatology, 2020)
Recessive dystrophic epidermolysis bullosa (RDEB) is a hereditary blistering disorder due to a lack of type VII collagen. At present, treatment is mainly supportive. To determine whether intravenous allogeneic bone marrow–derived mesenchymal stromal/stem cells (BM-MSCs) are safe in RDEB adults and if the cells improve wound healing and quality of life. We conducted a prospective, phase I/II, open-label study recruiting 10 RDEB adults to receive 2 intravenous infusions of BM-MSCs (on day 0 and day 14; each dose 2-4 × 106 cells/kg). BM-MSCs were well tolerated with no serious adverse events to 12 months. Regarding efficacy, there was a transient reduction in disease activity scores (8/10 subjects) and a significant reduction in itch. One individual showed a transient increase in type VII collagen. Open-label trial with no placebo. MSC infusion is safe in RDEB adults and can have clinical benefits for at least 2 months.